Poverty, environment, development: a many-patterned nexus - Nadkarni, M.V. (2000)
The thesis that poverty leads to environmental degradation and hence to more poverty deals with only one of the several patterns of the poverty-environment-development nexus prevailing in India and the third world. The other patterns include a trade-off between poverty alleviation and conservation of the environment; necessary conservation which hurts the poor, at least in the short run; development which aggravates both poverty and environmental degradation; and persistent poverty helping the cause of the environment. There are also heartening instances of this cause prospering side by side with that of poverty alleviation. - Reproduced
Keywords: Poverty - India; Poverty